(untitled) (International relations and international law Journal, 2016)
This article describes the new opportunities for economic development of the regions situated on the historical route of the Great Silk Way. The new route will run across the continent of Eurasia, crossing many countries. It affects 3 billion people, as well as linking the Asian, Pacific and Western European economic circles. The main goal of «economic factor of the Silk Way» – the creation of a new model of regional cooperation. The traditional model of regional cooperation in the first place allows for the creation of mutually beneficial trade and economic way agreements and the establishment of a common customs policy, and then the establishment of international institutions. The strategic concept of «economic way Silk Way» consists of five points: political connections of roads, free trade, monetary circulation and common aspirations of the people.